Use of A Blog-Based Content Management System (CMS) Application in the Dumpling Chips Culinary Business to Build the Entrepreneurial Spirit of University of Bengkulu Students - Ressti Nurfitriani; Puji Wahyu Ningsih; Ciawulan Sari; Herfani Herfani (CV. Media Inti Teknologi, 2023)
The purpose of the research is to improve promotional activities and to build the entrepreneurial spirit of students. The benefits of research are that the dumpling chip culinary business is not only known to rely on passing buyers or neighbors and can make online sales applications for dumpling chip culinary businesses. In this study, the method used was the qualitative method. The population and sample used are students of Bengkulu University. With the use of a blog-based content management system application, it can be beneficial for students who want to pursue a career in the business world. The use of this application awakens the entrepreneurial spirit of students, so they want to try it. In addition, this application makes it easy for us to buy goods only from home or anywhere, making it easier for customers when busy. The results of this research are expected to increase blog-based product sales and build a student entrepreneurial spirit.